Alternative approaches to human rights : the disparate historical paths of the European, inter-American and African regional human rights systems - Roberts, Christopher, 1982- (Cambridge : Cambridge University Press, 2023)
This book explores the comparative historical evolution of the European, Inter-American and African regional human rights systems. The book devotes attention to various factors that have shaped the systems: the different circumstances in which they were founded; the influence of major states and inter-state politics within their respective regions; gradual processes of institutional evolution; and the impact of human rights advocates and claimants. Throughout, the book devotes careful attention to the impact of institutional and procedural choices on the functioning of human rights systems. Overarchingly, the book explores the contextually-generated differences between the three systems, suggesting that human rights practice is less unitary than it might at times appear. Prescriptively, the book proposes that, contrary to the received wisdom in some quarters, the Inter-American system's dual-track approach may provide the most promising model in regards to future human rights system design.
Introduction -- Foundational moments -- Struggles -- Comparisons -- Conclusion.
Title from publisher's bibliographic system (viewed on 10 Nov 2022).
Keywords: International human rights courts -- Africa; International human rights courts -- America; International human rights courts -- Europe